PUBLIC WILLINGNESS TO PAY FOR HALAL CERTIFIED BEEF - Muhammad Dzakir Fiqi; Darwanto Darwanto (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
This research aims at analyzing the scale of public willingness to pay and the influence of age, income, awareness, perception, and religiosity on their willingness to pay the halal certified beef. This research was conducted in Jakarta with purposive sampling method and 100 respondents. The analysis method used in this research is descriptive statistical analysis, contingent valuated method and logit regression. The results show that 77 of respondents are willing to pay more for halal certified beef, while the other 23 are not. The average value of WTP obtained is 7% of the price of ordinary meat. The result of logit regression analysis shows that awareness variable has significant effect on willingness to pay halal certified beef, while the income, age, perception, and religiosity have no significant effect.